UJI EFEK LARVASIDA INFUSA BIJI SRIKAYA (Annona squamosa L.) TERHADAP LARVA Aedes aegypti - Surahma Asti Mulasari; Riris Subastian (Universitas Ahmad Dahlan, 2022)
Indonesia as a tropical country has optimal humidity and temperature that are favorable for survival, larval growth, and disease transmission. One of them is dengue hemorrhagic fever (DHF). The use of chemical insecticides does provide effective and optimal results in eradicating disease-causing vectors. So that control is carried out with biological (vegetable) insecticides which are safer, simpler and environmentally friendly. One of the most effective plant-based insecticides against Aedes aegypti larvae is sugar apple or Annona squamosa L. which is effective as a stomach poison and contact poison because of its active ingredients, namely annonain and squamosin. This study aims to determine the effect of larvicidal infusion of srikaya seeds (Annona squamosa L.) on Aedes aegypti larvae. The object of this research is 40 larvae of Aedes aegypti instar IV. Aedes aegypti larvae were exposed to infusion of Annona squamosa L. seeds for 16 hours with well water as a negative control and abate as a positive control. Data analysis used regression analysis to determine the effect of infusion on larvae and probit analysis to determine LC50.The results of this study showed that the infusion of Annona squamosa L. seeds had a killing power of Aedes aegypti larvae of p=0.001 with a straight line equation Y=9.095+67.143X. Probit analysis showed that LC50. is 17%. Meanwhile, Annona squamosa L. seed infusion was not as effective as abate.Conclusion: The infusion of Annona squamosa L. seeds has the power to kill Aedes aegypti larvae, LC50. The concentration of Annona squamosa L. seed infusion to kill Aedes aegypti larvae after 16 hours of treatment was at a concentration of 17%, and abate was more effective than Annona squamosa L. seed infusion.